IMPROVING THE EFFECTIVENESS OF AGRICULTURAL EXTENSION PROGRAMS THROUGH A WHATSAPP COMMUNICATION APPROACH IN MANULEA VILLAGE, SASITAMEAN DISTRICT, MALAKA REGENCY - Muti, Maria Magdalena; Olviana, Tomycho; Un, Paulus (Undana Press, 2025)
This study aimed to evaluate the effectiveness of a corn-farming agricultural extension program implemented through a digital communication approach using WhatsApp in Manulea Village, Sasitamean District, Malaka Regency. The study employed a mixed-methods approach combining qualitative and quantitative methods. Data were collected through interviews, observation, documentation, and questionnaires. A total of 38 farmers were selected purposively based on smartphone ownership, at least one year of farming experience, and participation in extension activities. The results showed that digital communication through WhatsApp helped disseminate agricultural information quickly, flexibly, and effectively. The extension program provided information related to the use of superior seeds, planting and crop maintenance techniques, fertilization, pest and disease control, and post-harvest processing. The effectiveness of the program was reflected in farmers’ adoption of several recommended corn cultivation technologies. However, several constraints remained, including limited farmer time, the relatively older age of some farmers, limited internet access in certain areas, and difficulties in obtaining adequate agricultural inputs. The program was generally considered moderately effective to effective, although several aspects, such as fertilizer use, technical training, and post-harvest practices, still require improvement. The study recommends that extension agents provide more intensive direct and online assistance, prepare flexible communication schedules, and that local governments support digital extension through the provision of digital infrastructure and information technology training for farmers.